The public distribution systems of foodgrains and implications for food security: A comparison of the experiences of India and China - Zhang-Yue Zhou; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
A comparative study of the public distribution systems of foodgrains in India and China is expected to reveal lessons and experiences that are valuable to policymakers. This is particularly important for developing countries in their endeavour to ensure food security. This paper undertakes such an exercise. The main features and developments of the two public distribution systems are first highlighted. This is followed by a comparative analysis of their similarities and differences. The role of public foodgrain distribution systems in ensuring food security is then evaluated. Finally, policy implications are drawn.
Keywords: I31; I38; Q11; Q18; 330; public distribution system; food security; poverty; food subsidy; India; China; Nahrungsmittelversorgung; Indien; China